Usòtåurah-®i åab, chåiståi-i paråi va chiråagh-i baråat va våakåavåi-i åan-i båa åayåin-i Siyåavashåan - Måihan§dåust, Muòhsin (Mashhad : Intishåaråat-i Taråanah, 2018)
Water--Mythology. ; Mythology, Iranian.
Includes bibliographical references (pages 257-260).
In Persian; some in English.
Keywords: Water -- Mythology; Mythology, Iranian; Mythology